Interaction between astrocytes and adult subventricular zone precursors stimulates neurogenesis - Lim, Daniel A. (The National Academy of Sciences, 1999)
Neurogenesis continues in the mammalian subventricular zone (SVZ) throughout life. However, the signaling and cell–cell interactions required for adult SVZ neurogenesis are not known. In vivo, migratory neuroblasts (type A cells) and putative precursors (type C cells) are in intimate contact with astrocytes (type B cells). Type B cells also contact each other. We reconstituted SVZ cell–cell interactions in a culture system free of serum or exogenous growth factors. Culturing dissociated postnatal or adult SVZ cells on astrocyte monolayers—but not other substrates—supported extensive neurogenesis similar to that observed in vivo. SVZ precursors proliferated rapidly on astrocytes to form colonies containing up to 100 type A neuroblasts. By fractionating the SVZ cell dissociates with differential adhesion to immobilized polylysine, we show that neuronal colony-forming precursors were concentrated in a fraction enriched for type B and C cells. Pure type A cells could migrate in chains but did not give rise to neuronal colonies. Because astrocyte-conditioned medium alone was not sufficient to support SVZ neurogenesis, direct cell–cell contact between astrocytes and SVZ neuronal precursors may be necessary for the production of type A cells.